Legal regulation of public procurement in the EU and the EAEU: Trends to digitalization - R. A. Kasyanov; A. P. Puchkova (Цифровое право, 2022)
The article touches upon some problems of legal regulation of public procurement in two organizations — the European Union (EU) and the Eurasian Economic Union (EAEU). A wide EU experience in public procurement regulation could be helpful for the EAEU, as it is facing now the same problems as the EU did, for example the digitalization of public procurement.Russian researchers often refer to European experience in order to find best practices, but the European experience in the legal regulation of public procurement is poorly examined by Russian authors. The aim of the study is to compare the process of digitalization of public procurement regulation in the EU and in the EAEU, highlight the EU instruments in this sphere which could be useful for the EAEU and point some common features and differences of the digitalization process in the sphere of public procurement in these organizations.In the article the authors compare different fields of public procurement legal regulation in the EU and in the EAEU and both general and specific instruments of digitalization in the sphere of public procurement existing in the EU and in the EAEU. The study is based on the analysis of the EU law and legal precedents.As a result the authors make a conclusion that some EU instruments of public procurement legal regulation could be applied in the EAEU or its member states law considering the difference in historical development of public procurement legal regulation of the organizations and positive experience of the EAEU member states.